Observational cohort study of perinatal outcomes of women with COVID-19. Issue 12 (December 2022) - Al-Hajjar, Sami; Ibrahim, Lina; Kurdi, Wesam; Tulbah, Maha; Alnemer, Maha; Bin Jabr, Mohammed; Elsaidawi, Weam; Binmanee, Abdulaziz; Ali, Mohanned; Bukhari, Hanifa; Altuwaijri, Leena; Allaboon, Raneem; et al.
Abstract: Background: Understanding the impact of SARS-CoV-2 infection on pregnancy outcomes and of pregnancy on COVID-19 outcomes is critical for ensuring proper prenatal and antenatal care. No similar studies have been published in Saudi Arabia. Methods: We performed a prospective cohort study of pregnant women with confirmed SARS-CoV-2 infection who presented at King Faisal Specialist Hospital and Research Center (KFSHRC) in Riyadh, Kingdom of Saudi Arabia. COVID-19 staging was performed, pregnancy-related complications were assessed, and neonatal infection was evaluated. Results: We enrolled 81 patients (mean age 31.75 years, SD 5.25) of which there were 17 cases in the first trimester, 20 in the second trimester, and 34 in the third trimester. The distribution of COVID-19 severity was 40 patients with Stage A, 36 with Stage B, 4 with Stage C, and 1 with Stage D. Complications were pregnancy loss in 2 patients (one in each first and second trimester) and 1 fetal death after 20 weeks of pregnancy, 7 patients with fetal growth restriction, and 8 with pre-term delivery. Conclusions: We did not observe an unusual frequency of pregnancy-related complications due to SARS-CoV-2 infection in this high-risk obstetric population and there was no evidence of vertical transmission in newborns from women who delivered while positive for the virus.